Evaluating R&D performance of EU countries using categorical DEA - Karadayi, Melis Almula; Ekinci, Yeliz (Routledge Journals, Taylor & Francis Ltd, 2019)
Over the coming decade, Research and Development (R&D) performance will be the key component of bringing innovation and the determinant of global competitiveness of nations. Therefore, this paper presents categorical Data Envelopment Analysis (DEA) for evaluating R&D performance of European Union (EU) countries. We utilise the output-oriented constant returns to scale (CRS) and variable returns to scale (VRS) DEA models with categorical data, namely, CAT-O-C and CAT-O-V models. In addition to DEA based framework, to examine the relationship between R&D performance and political-regulatory-economic situation of the countries; three research hypotheses are stated and their results are analysed. Policy implications about R&D activities can be derived for EU countries from the findings of this study.
Keywords: Categorical Data; Data Envelopment Analysis; Efficiency; R&D; Eu; Development Efficiency; Cross-Country; Innovation; Impact; China